Mesenchymal Stem Cells Seeded on Cross‐Linked and Noncross‐Linked Acellular Porcine Dermal Scaffolds for Long‐Term Full‐Thickness Hernia Repair in a Small Animal Model. Issue 7 (4th December 2013) - Mestak, Ondrej; Matouskova, Eva; Spurkova, Zuzana; Benkova, Kamila; Vesely, Pavel; Mestak, Jan; Molitor, Martin; Pombinho, Antonio; Sukop, Andrej
Abstract Biological meshes are biomaterials consisting of extracellular matrix that are used in surgery particularly for hernia treatment, thoracic wall reconstruction, or silicone implant‐based breast reconstruction. We hypothesized that combination of extracellular matrices with autologous mesenchymal stem cells used for hernia repair would result in increased vascularization and increased strength of incorporation. We cultured autologous adipose‐derived stem cells harvested from the inguinal region of Wistar rats on cross‐linked and noncross‐linked porcine extracellular matrices. In 24 Wistar rats, a standardized 2 × 4 cm fascial defect was created and repaired with either cross‐linked or noncross‐linked grafts enriched with stem cells. Non‐MSC‐enriched grafts were used as controls. The rats were sacrificed at 3 months of age. The specimens were examined for the strength of incorporation, vascularization, cell invasion, foreign body reaction, and capsule formation. Both materials showed cellular ingrowth and neovascularization. Comparison of both tested groups with the controls showed no significant differences in the capsule thickness, foreign body reaction, cellularization, or vascularization. The strength of incorporation of the stem cell‐enriched cross‐linked extracellular matrix specimens was higher than in acellular specimens, but this result was statistically nonsignificant. In the noncross‐linked extracellular matrix, the strength of incorporation was significantly higher in the stem cell group than in the acellular group. Seeding of biological meshes with stem cells does not significantly contribute to their increased vascularization. In cross‐linked materials, it does not ensure increased strength of incorporation, in contrast to noncross‐linked materials. Owing to the fact that isolation and seeding of stem cells is a very complex procedure, we do not see sufficient benefits for its use in the clinical setting.